New macromolecular structures based on benzene core, synthesis and characterization - Ali, Mohammed Hadi; Torun, Lokman (NATL INST SCIENCE COMMUNICATION & INFORMATION RESOURCES-NISCAIR, 2021)
A series of new compounds based on benzene ring as a central core substituted with aromatic compounds such as (benzene and pyridine) and three armed of 2-chloro-4,6-bis((3,7-dimethyloct-6-en-1-yl) oxy)-1,3,5-triazine, have been obtained by sequential nucleophilic substitution of chlorine atoms in cyanuric chloride. The substitution at the acetylenic periphery on the central benzene ring has been achieved efficiently by Sonogashira coupling. Equimolar mixtures of the six-armed compounds based on the benzene core with the complementary 4-dodecyloxybenzoic acid, which already possessed liquid crystal property, has resulted in an organic salt. The obtained organic salts have been investigated by polarizing optical microscopy (POM) and differential scanning calorimetry (DSC). The synthesized compounds have been confirmed by spectroscopic methods (H-1 and C-13 NMR and mass spectromery).
Keywords: Triazine; liquid crystals; hydrogen bonding; synthesis; characterization; Chemistry